A Case Report of Non-puerperal Uterine Inversion - Arab, Maliheh; Talayeh, Maryam; Teymoordash, Somayyeh N.; Ghavami, Behnaz; Mahmoodi, Sheema (Current Women's Health Reviews, 2023)
Objective: Non-puerperal uterine inversion is a rare occurrence. The common etiology for this condition is uterine sarcoma, endometrial carcinoma, and myoma. Case Presentation: This case is a 44-year-old woman with a protruding malodorous vaginal mass, abdominal pain, and urinary retention. Total hysterectomy with bilateral salpingectomy was performed. Conclusion: Diagnosis of uterine inversion might be difficult and requires a high index of suspicion.
Keywords: Uterine inversion